The haustorium as a driving force for speciation in thallus-forming Laboulbeniomycetes - Haelewaters, Danny; Lubbers, Maarten; De Kesel, André (IMA fungus, 2022)
Laboulbeniomycetes is a class of fungi that have obligate associations with arthropod hosts, either for dispersal (order Pyxidiophorales) or as biotrophic parasites (orders Herpomycetales and Laboulbeniales). Here, we focus on Herpomycetales and Laboulbeniales, which include fungi that form thalli, 3-dimensional, multicellular units of 1000 s of cells. Based on recently published data regarding patterns of speciation, we present the One-Host-One-Parasite model (1H1P) for haustorial thallus-forming Laboulbeniomycetes. We hypothesize that taxa with haustoria, rhizoidal structures that make contact with the host's body cavity, have very strict host specificity. For taxa without haustoria, the microhabitat-as selected by the host-governs host shifting, presence or absence of the fungus, abundance, effective host range, and geographic distribution. We make suggestions for future research including fluorescent labeling of waxy lipids and mass spectrometry. These techniques have the potential to generate the data necessary to evaluate the here proposed 1H1P hypothesis for Herpomycetales and Laboulbeniales.
Keywords: Integrative taxonomy; Haustorium; Laboulbeniales; Herpomyces; One-Host-One-Parasite; Host specificity; Ectoparasitic fungi